Analisis Pengaruh Karakteristik Bank terhadap Profitabilitas Bank pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Serly Serly; Tiffany Tiffany (Faculty of Economics, Universitas Internasional Batam, 2019)
This research has a purpose to analyze the effect of bank characteristics on bank profitability in company listed on Indonesia Stock Exchange. Return on assets, return on equity, and net interest margin as the proxy of profitability as the dependent variable. The independent variables are non-performing loans, loan loss provision, inflation rate, deposits, interest margin, bank size, capital ratio, and loans. The sample processed in this research are bank company listed in Indonesia Stock Exchange within 2013-2017. The data is processed by a statistic software with panel regression method to be analyzed. The result shows that non-performing loans, loan loss provision, inflation rate, deposits, bank size, and loans had no significant effect on return on assets. In contrast, interest margin had a significant negative effect on return on assets. Non-performing loans, capital ratio, and loans had significant positive effect on return on equity, whereas loan loss provision and deposits had significant positive effect on return on equity. But inflation rate, interest margin, and bank size had no significant effect on return on equity. Non-performing loans, capital ratio, and loans had significant positive effect on net interest margin, whereas loan loss provision and deposits had significant positive effect on net interest margin. But inflation rate, interest margin, and bank size had no significant effect on net interest margin.